Instability and evolution of the magnetic ground state in metallic perovskites GdRh3C1−xBx - Pandey A.; Singh A.K.; Dan S.; Ghosh K.; Das I.; Tripathi S.; Kumar U.; Ranganathan R.; Johnston D.C.; Mazumdar C. (My University, 2025)
We report investigations of the structural, magnetic, electrical transport, and thermal properties of five compositions of the metallic perovskite GdRh3C1−xBx (0.00 < x < 1.00). Our results show that all five compositions undergo magnetic ordering at low temperatures, but the nature of the ordered state is significantly different in the carbon- and the boron-rich compositions, where the former shows signatures of an amplitude-modulated magnetic structure and the latter exhibits evidence of an equal-moment incommensurate antiferromagnetic ordering. We also observe a remarkable field-dependent evolution of conduction carrier polarization in the compositionally disordered compounds. The outcomes indicate that this system is energetically situated in proximity to a magnetic instability where small variations in the control parameter(s), such as the lattice constant and/or electron density, lead to considerably different ground states. ©2020 American Physical Society